2020
DOI: 10.1186/s12879-020-05274-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of pregnant women with COVID-19: a systematic review and meta-analysis

Abstract: Background: The recent COVID-19 outbreak in Wuhan, China, has quickly spread throughout the world. In this study, we systematically reviewed the clinical features and outcomes of pregnant women with COVID-19. Methods: PubMed, Web of Science, EMBASE and MEDLINE were searched from January 1, 2020, to April 16, 2020. Case reports and case series of pregnant women infected with SARS-CoV-2 were included. Two reviewers screened 366 studies and 14 studies were included. Four reviewers independently extracted the feat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 45 publications
5
71
1
7
Order By: Relevance
“…Since, several articles have reported that the possibilities of vertical transmission (37,38), highlighting the importance of long-follow up of newborns (39). To clarify the vertical transmission and neonatal outcomes due to SARS-CoV-2 infection; we further compared our findings with other recently published systematic review and meta-analyses (38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Raschetti et al (38) evaluated neonatal outcomes from 74 published articles in where 30% of neonates were reported in the possible vertical transmission and 70% were from environmental sources ( Table 4).…”
Section: Comparison With Recent Findingsmentioning
confidence: 98%
“…Since, several articles have reported that the possibilities of vertical transmission (37,38), highlighting the importance of long-follow up of newborns (39). To clarify the vertical transmission and neonatal outcomes due to SARS-CoV-2 infection; we further compared our findings with other recently published systematic review and meta-analyses (38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Raschetti et al (38) evaluated neonatal outcomes from 74 published articles in where 30% of neonates were reported in the possible vertical transmission and 70% were from environmental sources ( Table 4).…”
Section: Comparison With Recent Findingsmentioning
confidence: 98%
“…We expect to increase our study sample in the following months and thus provide further results. The main strength of this study is that it was conducted in one of the six reference centres for the treatment of COVID-19 in women in Lombardy, the first region to be affected by the disease in Europe and one of the areas with the highest diffusion rate of infection [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent studies, the most common symptoms of pregnant women with COVID‐19 were fever and cough. [ 8 ] Pregnant women with these symptoms or with a history of contact with suspected or confirmed cases should visit fever clinics to receive tests for COVID‐19.…”
Section: Diagnosis Of Covid‐19 In Pregnant Womenmentioning
confidence: 99%
“…[ 17 ] A meta‐analysis included 236 pregnant women with COVID‐19 demonstrated that 71% patients had positive CT finding. [ 8 ] Chen et al. have found 88 of the 111 pregnant women in Wuhan (79%) who underwent chest CT had infiltrates in both lungs.…”
Section: Diagnosis Of Covid‐19 In Pregnant Womenmentioning
confidence: 99%